Preseganje spolnih stereotipov v sodobni slovenski komediji (Ditka - Milena - Boris) - Pezdirc Bartol, Mateja (Amfiteater (Ljubljana), 2024)
Comedy has always paid much attention to the depiction of gender relations, love affairs and the happy ending that a wedding represents. In this paper, the author explores to what extent 21st-century Slovenian comedy tracks the changing roles of men and women in the family and society and diverges from traditional representations of the body and sexuality. The analysis covers Slovenian comedies that question social constructions of genders, roles and occupations, play with gender stereotypes or go beyond them in some of their aspects: Denis in Ditka by Tone Partljič; Boris, Milena, Radko by Dušan Jovanović; and jerebika, štrudelj, ples pa še kaj by Simona Semenič. In these comedies, gender relations form the central theme, and a female character plays the leading role.
Keywords: body; comedy; construction of social and gender roles; contemporary Slovenian drama; Dušan Jovanović; komedija; konstrukcija družbenih in spolnih vlog; ljubezen; love; Simona Semenič; sodobna slovenska dramatika; telo; Tone Partljič